Antle Discovers his Voice: Examining Uses of Oral Language Resources for Mi’kmaw Learners - McKee, Lori; Lunney Borden, Lisa; Gould, Blaire; Laughlin, Jarrett; Morris, Ramona (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
This article shares findings from the first phase of program evaluation of Antle, a holistic language resource for teaching, learning and assessment. The program evaluation was guided by understandings that appreciate the interconnections of literacies and identities and is situated within a decolonizing framework that recognizes the transformation of Indigenous knowledges as essential. A quantitative and qualitative analysis was conducted. Analysis revealed the educators valued Antle but did not use the resource consistently. Recommendations include providing information to teachers about connections between literacies theories, curriculum outcomes, and program activities, and additional support for implementation. This article serves as an invitation to researchers and educators across Canada to rethink literacy assessment practices.